Long-term benefits to psychological health and well-being after ceremonial use of Ayahuasca in Middle Eastern and North African immigrants and refugees - Lowe, Matthew X.; Kettner, Hannes; Jolly, Del R. P.; Carhart-Harris, Robin L.; Jackson, Heather (Frontiers in Psychiatry, 2024)
Background. Refugees and immigrants can experience complex stressors from the process of immigration that can have lasting and severe long-term mental health consequences. Experiences after ayahuasca ingestion are shown to produce positive effects on psychological wellbeing and mental health, including anecdotal reports of improved symptoms of trauma and related disorders. However, data on the longitudinal health impact of naturalistic ayahuasca use in Middle Eastern and North African (MENA) immigrant and refugee populations is limited.The current longitudinal online survey study was conducted to gather prospective data on ceremonial ayahuasca use in a group (N = 15) of primarily female MENA immigrants and refugees and to provide further insight into the patterns and outcomes surrounding that use. The study sought to assess self-reported changes in physical and mental health, well-being, and psychological functioning, examine relationships between aspects of individual mindset (e.g., psychedelic preparedness) prior to ayahuasca use and observed outcomes during (e.g., subjective drug effects) and afterwards (i.e., persisting effects), characterize risks and negative experiences, and describe trauma exposure and personal history.Results/Outcomes. Our findings revealed ceremonial use of ayahuasca is associated with significant improvements in mental health, well-being, and psychological functioning, including reductions in depression, anxiety, and shame, and increases in cognitive reappraisal and selfcompassion. Most participants reported no lasting adverse effects and experienced notable positive behavioral changes persisting months after ingestion.Conclusions/Interpretation. While preliminary, results suggest naturalistic ayahuasca use might hold therapeutic potential for MENA populations exposed to trauma prior to and during the process of migration.Declaration of Interest/Funding. None.